Analyzing the Functions of Mast Cells In Vivo Using 'Mast Cell Knock-in' Mice - Gaudenzio, Nicolas (J Vis Exp, 2015)
Mast cells (MCs) are hematopoietic cells which reside in various tissues, and are especially abundant at sites exposed to the external environment, such as skin, airways and gastrointestinal tract. Best known for their detrimental role in IgE-dependent allergic reactions, MCs have also emerged as important players in host defense against venom and invading bacteria and parasites. MC phenotype and function can be influenced by microenvironmental factors that may differ according to anatomic location and/or based on the type or stage of development of immune responses. For this reason, we and others have favored in vivo approaches over in vitro methods to gain insight into MC functions. Here, we describe methods for the generation of mouse bone marrow-derived cultured MCs (BMCMCs), their adoptive transfer into genetically MC-deficient mice, and the analysis of the numbers and distribution of adoptively transferred MCs at different anatomical sites. This method, named the ‘mast cell knock-in’ approach, has been extensively used over the past 30 years to assess the functions of MCs and MC-derived products in vivo. We discuss the advantages and limitations of this method, in light of alternative approaches that have been developed in recent years.